The relationship of student's use patterns and assessment of the IKIP Sanata Dharma library resources, facilities and services to library use - Arief, Bernard B.; Buenrostro, Juan Jr. C.; Hidalgo, Namnama P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1992)
This study attempts to analyze the relationship of student library use to the resources, facilities, and services of the IKIP Sanata Dharma Library, Yogyakarta, Indonesia, as assessed by the students. The objectives of the study are: 1) To determine the status of the IKIP Sanata Dharma Library resources, facilities, and services as evaluated by the students; 2) To find out if a relationship exists between these library resources, facilities and services and student library use; 3) To determine whether student personal factors were related to student library use.
This study used the normative survey research method with a questionnaire as a tool for gathering data. The subjects of the study were the students of the IKIP Sanata Dharma enrolled in the second semester, 1991-1992. The respondents were randomly sampled from about ten percent of the total student population. They were predominantly females, from 21 to 24 years of age from the colleges of Social Sciences, Education, Language and Letters and Exact Sciences.
The findings of the study show that almost all of the respondents (95.7 per cent) used the library and most of them (63.9 per cent) visited it frequently. Majority of the respondents were satisfied with the IKIP Sanata Dharma Library services. They judged the reference service provided by the library staff to be good. Majority of the respondents rated the book and periodical collections of the library to be adequate. Majority of the respondents claimed that the Reading/Reference Room was large and the number of seats in the Reading/Reference Room was adequate.
In general, library-related factors (independent variable), such as library borrowing/returning hours, number of books on loan and reference service provided by the library staff have no significant relationship with the student library use; thus, the null hypothesis that there is no significant relationship between the students' assessment of the library and library use was accepted.
With regards to student personal factors (independent variables) such as college, age, distance of residence, and academic performance, the result of the statistical test showed that these factors, with the exception of sex, have no significant relationship with the library use. Thus, the null hypothesis that the personal characteristics of students are not related to the students' use or non-use of the library was accepted.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: IKIP Sanata Dharma. Library--Information services; Library resources,.; Library use studies--Indonesia.